High frequency magnetic behavior through the magnetoimpedance effect in CoFeB/ (Ta, Ag, Cu) multilayered ferromagnetic thin films - Marques, Manilo Soares (2012)
We investigate the structural and magnetic properties and the magnetoimpedance effect of CoFeB/(Ta, Ag, Cu) multilayered thin films grown by magnetron sputtering. It is noticed that the peak of maximum magnetoim- pedance ratio values for a given frequency, as well as its position in frequency, is varied according to the used non-magnetic metal. For the CoFeB/Ta and CoFeB/Ag multilayered films, peaks of 30% and 27%, respectively, are observed at localized frequency ranges. For the CoFeB/Cu multilayer, slightly smaller values are verified, but for a wide frequency range. The magnetoimpedance results are analyzed in terms of the mechanisms responsible for the impedance variations at different frequency ranges and the magnetic and structural properties of the multilayer